Cyanoximes as effective and selective co-crystallizing agents - Aakeröy, Christer B. (2009)
The ability of cyanoxime-based synthons to act as versatile synthetic tools for the construction of co-crystals is demonstrated through the preparation and structural characterization of seven co-crystals. Cyanoximes can bind effectively to both five-membered and six-membered N-heterocyclic hydrogen-bond acceptors, and they also display selectivity towards the best acceptor (as determined using semi-empirical AM1 calculations) in ditopic compounds.